Application of nanoparticles for targeted management of pests, pathogens and disease of plants - Abdulrazaq Izuafa; Konjerimam Ishaku Chimbekujwo; Ramat Onyenoyiza Raji; Oluwafemi Adebayo Oyewole; Rasheed Olakitan Oyewale; Olabisi Peter Abioye (Plant Nano Biology, 2025)
Pest and disease infestations pose a significant threat to global food security, drastically lowering plant health and agricultural productivity. Conventional pest management methods, primary reliant on chemical pesticides and fertilizers, often present limited long-term effectiveness and are associated with significant environmental and health risks. In response to these challenges, nanotechnology has arisen as a revolutionary instrument in modern agriculture. Nanoparticles (NPs) have unique physical and chemical properties such as high surface area, adjustable surface charge, and controlled release patterns. These properties enable precise delivery of farm chemicals to specific plant tissues or pest targets. This approach improves effectiveness and reduces unintended environmental exposure. Nanoparticles application in the form of nanofertilizers and nanopesticides provides a sustainable alternative to traditional agricultural inputs, offering controlled release, increased bioavailability, and decreased toxicity. This method not only promotes pest and disease control in plants but reduce toxicity. This review explores the role of nanoparticles in pest and disease managements, their mechanisms of action, and their potential contributions to environmental conservation and agricultural sustainability.